Especies de Eimeria (Eucocddida: Eimeriidae) en la rata de milpa Sigmodon hispidus de Costa Rica - Castro, Alfredo (Universidad de Costa Rica, 1998)
Cotton rats (Sigmodon hispidus) were collected from Ojo de Agua, Alajuela (N=74) and Cañas, Guanacaste (N=29). Feces had 31 E. sigmodontis, nine E. tuskegeensis, eight E. roperi, three E. webbae and two Eimeria sp. This is the first repor! of tbese coccidian parasites for Costa Rica